Highly efficient visible light active Cu–ZnO/S-g-C3N4 nanocomposites for efficient photocatalytic degradation of organic pollutants. Issue 59 (19th November 2021) - Javed, Mohsin; Qamar, Muhammad Azam; Shahid, Sammia; Alsaab, Hashem O.; Asif, Salma
Abstract : The photocatalytic activity of photocatalyst is severely hampered by limited visible light harvesting and unwanted fast recombination of photogenerated e − and h + . Abstract : The photocatalytic activity of photocatalysts is severely hampered by limited visible light harvesting and unwanted fast recombination of photogenerated e − and h + . In the current study, the photocatalytic efficiency of Cu–ZnO/S-g-C3 N4 (CZS) nanocomposites was investigated against MB dye. The composite materials were designed via chemical co-precipitation method and characterised by important analytical techniques. Distinctive heterojunctions developed between S-g-C3 N4 and Cu–ZnO in the CZS composite were revealed by TEM. The synthesized composites exhibit a huge number of active sites, a large surface area, a smaller size and better visible light absorption. The considerable enhancement in the photocatalytic activity of CZS nanocomposites might be accredited to the decay in the e–h pair recombination rate and a red shift in the visible region, as observed by PL and optical analysis, respectively. Furthermore, the metal (Cu) doping into the S-g-C3 N4 /ZnO matrix created exemplary interfaces between ZnO and S-g-C3 N4, and maximized the photocatalytic activity of CZS nanocomposites. In particular, CZS nanocomposites synthesized by integrating 25% S-g-C3 N4 with 4% Cu–ZnO (CZS-25 NCs) exhibited the 100% photocatalytic degradation of MB in 60 minutes under sunlight irradiation. After six cycles, the photocatalytic stability of CZS-25 NCs was excellent. Likewise, a plausible MB degradation mechanism is proposed over CZS-25 NCs based on photoluminescence and reactive species scavenger test observation. The current research supports the design of novel composites for the photocatalytic disintegration of organic contaminants.